Usability testing of the Si Salto application using the heuristic evaluation method - Hengki Ternando; Akhamd Khudri (Jurnal Mantik, 2023)
Si Salto application is one of the platforms used to make the process of ordering services online, with this system the process of ordering services will be well planned. By paying attention to the user, an appropriate and appropriate information system can be created for the user, so that it will lead to satisfaction by the user. This technology needs to be continuously evaluated using the Heuristic Evaluation method by testing sample users whose results will then be verified and validated using the Heuristic Evaluation technique. With this evaluation, it is hoped that problems related to deficiencies in usability will be found which will then be used as a reference in drawing recommendations to improve the quality of the application. Usability evaluation to measure efficiency, effectiveness, and assess user satisfaction. User experience is several important factors in building an application. Without the right appearance and user experience, it can result in users switching to other similar applications. This study has a target to evaluate the user experience of the Si Salto application using the Heuristic Evaluation and Usability Testing methods.